THE SOCIAL IMPORTANCE OF DEVELOPING SANOGENIC THINKING IN A PERSON (Web of Teachers: Inderscience Research, 2025)
This article presents the scientific views of scientists on the importance of thinking and thinking, the social psychological features of healthy thinking in the development of the individual.